Anti-collapse performance of steel frames with RWS connections under a column removal scenario. (15th January 2021) - Lin, Shentong; Qiao, Huiyun; Wang, Jinpeng; Shi, Jiahao; Chen, Yu
Highlights: The behaviours of the RWS connections in progressive collapse are investigated. The RWS connections trend to fracture in two area with extreme stress focus. Two flexural failure were observed in the RWS connections depending on web opening parameters. .The RWS connections developed catenary action with an interrupted failure The RWS connections performed higher deformability than the welded web connections. Abstract: The spread of an initial local failure from load-carrying member to other members in system when subjected to abnormal load, eventually resulting the progressive collapse of an entire structure. This paper presents an experimental and parametric study on the anti-collapse performance of moment resisting frames (MRFs) with reduced-web-section (RWS) connections under critical column removal scenario. Factors influencing robustness and rotational capacity in these connections under Vierendeel failure are analyzed. A total of 14 laboratory tests on steel beam-column connections with complete joint penetrations are presented; one test was conducted with solid beam connections, while the others were designed to have RWS connections with different circular web openings geometric parameters. Comprehensive finite models are then implemented to further interpret the obtained test results. The test results demonstrated that vertical resistance against the applied load atop the failed columns was totally composed of flexural action (FA) in the early stages, and it became catenary action (CA) as the vertical displacement of the failed column increased. There are two typical failure modes, continuous failure in the beam-column joint region generated by the weld line fracture and interrupted failure in RWS connections generated by the fracturing of a perforated section, and the different failure modes determine whether the system can develop meaningful catenary action when the initial fracture occurs. Specimens with openings exhibited multiple peak loads because of the repeated occurrence of local damage in the beam-column connection. RWS connections with local failure near the openings were capable of developing deformability and resistance associated with CA when the dimensions and location parameters of the opening are controlled within a suitable range, and the rotational capacities of these connections were larger than the connection with solid beams.